Toll-Like Receptor Stimulation by MicroRNAs in Acute Graft-vs.-Host Disease - Zitzer, Nina C.; Garzon, Ramiro; Ranganathan, Parvathi (Frontiers in Immunology, 2018)
Acute graft-versus-host disease (aGVHD) is a frequent complication of allogeneic hematopoietic stem cell transplantation (allo-HSCT), accounting for substantial morbidity and mortality associated with this treatment modality. The pathogenesis of aGVHD involves a complex cascade of humoral and cellular interactions in which donor T cells target HLA mismatched host tissues, causing tissue injury through secretion of pro-inflammatory cytokines and induction of direct cytotoxicity. Toll-like receptors (TLRs) are key components of the innate immune system that recognize endogenous danger-associated molecular patterns (DAMPs) and exogenous pathogen-associated molecular patterns (PAMPs). Patients receiving conditioning chemotherapy and/or whole-body irradiation prior to all-HSCT are prone to gastrointestinal damage and translocation of microbiota across compromised intestinal epithelium, resulting in release of PAMPs and DAMPs. These “danger signals” play critical roles in disease pathogenesis by both initiating and propagating aGVHD through dendritic cell maturation and alloreactive T cell responses. There are 10-15 TLRs identified in mammalian species, a subset of which recognize single-stranded RNA (ssRNA) and serve as a key component of viral immunity. Recently, ssRNAs other than those of viral origin have been investigated as potential ligands of TLRs. MicroRNAs (miRs) are short (19-24 nt) non-coding RNAs that play critical roles in a variety of diseases. While traditionally miRs post-translationally modulate gene expression, non-canonical functions such as regulating TLR stimulation by acting as TLR ligands have been described. Here, we review the role of TLRs in aGVHD pathogenesis, the function of miRs in TLR stimulation, and the recent literature describing miRs as TLR ligands in aGVHD.